Cryptocurrency according to the principles of usul al-fiqh: a critical analysis by Mohd Daud Bakar - Othman Sahalan,; Muhammad Adib Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
There are various views concerning the cryptocurrency issue. The majority of scholars and world Islamic bodies, such as Dar al-Iftā ‘al-Miṣriyyah (Egypt), Dar al-Iftā’ al-Falasteeniyya (Palestine) and the Turkish Directorate of Religious Affairs, do not permit cryptocurrency for various reasons, including the existence of uncertainty (gharar), risk (khatar) and the fact that it facilitates (wasilah) the crime of fraud and money laundering. However, some Islamic financial and religious scholars do permit it. One scholar who views cryptocurrency positively and believes that it should be permitted is Mohd Daud Bakar, who is the Chairperson of the Shariah Advisory Council of Securities Commission Malaysia (SC) and former Chairperson of the Shariah Advisory Council for Bank Negara Malaysia (BNM). He is also former President of the International Islamic University (IIUM) and the chairperson or international Shariah advisor at various financial institutions around the world, including the S&P Islamic Index and Dow Jones Islamic Market Index (New York). His extensive experience of more than 25 years in this dynamic field has made him a leading and important reference expert. In 2015, in a report released by the Global Islamic Finance Report (GIFR), he ranked sixth among the world’s 10 Islamic finance experts. This success has made him an expert, not only in the field of Usul al-Fiqh which is the core knowledge base of Islam, but also beyond the field of Islamic finance and law. This paper analyses the validity of Mohd Daud Bakar’s views on cryptocurrencies within the scope of Usul al-Fiqh according to the ‘illah, ‘urf, sad zarai’ and fatḥ zarāi’ methods. This qualitative study had obtained data from Facebook Live video recordings, reports and articles, which were then analysed using the descriptive content analysis method. It can be concluded from an ‘illah (legal operative cause) aspect that there is no acceptable ‘illah for banning this currency. From the point of view of al-’urf, cryptocurrencies are acceptable and do not contradict the principles of Shariah. Whereas from the point of view of sad zarāi’, this study found no solid evidence that it could lead to deleterious circumstances other than mere conjecture and assumption, hence, the introduction of cryptocurrencies should be permitted or made accessible. He also suggested the use of the fath zarāi’ method, which is better suited for creating opportunities for innovation and creativity of financial products based on financial technology (fintech). Finally, he mentioned about the permissibility of cryptocurrency as a medium of exchange even if it does not become the legal currency of a country.